Tinea incognito: Epilogue of inadequate diagnostics and therapy - Božić Srna G.; Milošević Nataša Z.; Bukvić-Šajinović Aleksandra S.; Vesković Dunja M.; Vujanović Ljuba M. (Srpsko lekarsko drustvo, 2024)
Introduction: Tinea incognito is a form of the disease Tinea corporis, and it is a superficial fungal skin infection caused by dermatophytes. It occurs in cases when clinical signs of the condition are misdiagnosed, and treatment with local and/or systemic corticosteroid therapy is administered, leading to the advancement of disease with an altered clinical status that persists for a long time and requires prolonged systemic treatment. Case Report: We present a 71-year-old patient who came for examination due to skin changes that appeared a year ago. The changes were localized on the extensors of the forearm, flexor side of the wrist joint, and lower part of the thighs in the form of erythematous and scaly plaques, partially merged on the forearm, and individual, annular erythematous plaques with pronounced peripheral borders and signs of central regression. The patient was diagnosed with Psoriasis vulgaris. He was treated with systemic retinoids (acitretin, Neotigason caps a 25 mg, Teva B.V.) over the course of 5 months, and with topical corticosteroids (mometazon, Elocom 1 mg/g mast, Organon Heist B.V.) over the course of ten months. Due to the worsening of the local findings, the patient was referred to the Clinic of Dermatovenereology Diseases of the Clinical Center of Vojvodina, where a preliminary diagnosis of Tinea incognito was established. A mycological examination was performed, during which the direct mycological findings were positive. The patient was treated with topical (terbinafine, Lamisil 10 mg/g krem, GSK Consumer Healthcare SARL) and systemic (flukonazol, Diflucan caps a 50 mg, Fareva amboise) antifungals, after which there was complete regression of changes on the skin. Conclusion: Tinea incognito is a superficial fungal skin infection, which occurs due to inadequate therapy prescribed for Tinea corporis. Fungal infections of the skin and skin adnexa are relatively common. Diagnosis is established through a detailed medical history, physical examination, and mycological examination. Timely application of topical and/or systemic antifungals leads to complete regression of skin changes. When the disease goes unrecognized and is treated with inadequate medications, it may progress into a distinct (atypical) form known as Tinea incognito.